2009
DOI: 10.2478/v10042-009-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptin concentrations in patients with polycystic ovary syndrome before and after met-formin treatment depending on insulin resistance, body mass index and androgen con-centrations--introductory report.

Abstract: Polycystic ovary syndrome (PCOS) is an endocrinological and metabolic disorder which may concern about 3-8 % of women. Some PCOS women have the increased leptin concentration in blood serum. Leptin concentration is higher in patients with high body mass index (BMI) and impaired tissue sensitivity to insulin. The aim of this study was to determine leptin concentrations in PCOS patients before and after metformin treatment depending on BMI, insulin resistance calculated on the basis of the Homeostasis Model Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, the effect of metformin on adipocytokine levels remains controversial. Some studies reported positive results [ 27 30 , 34 40 ], whereas others found no significant changes in adipocytokine levels after metformin administration [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of metformin on adipocytokine levels remains controversial. Some studies reported positive results [ 27 30 , 34 40 ], whereas others found no significant changes in adipocytokine levels after metformin administration [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that metformin treatment increased adiponectin plasma levels in women with polycystic ovary syndrome (PCOS) [23] and T2DM patients [24] while metformin treatment tends to decrease IL-6 plasma levels [23] as well as circulating levels of leptin [25] in PCOS patients, and significantly reduces resistin and TNF-α plasma levels [24] in T2DM patients. Moreover, metformin inhibition of TNF-α-induced IL-6 secretion was abolished after silencing of AMPKα1 in human umbilical vein endothelial cells [26].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with troglitazone did not seem to alter leptin levels (Mantzoros et al 1997). By contrast, administration of metformin, an insulin sensitizer widely used for the treatment of T2DM, considerably reduced serum leptin concentrations in obese (MorinPapunen et al 1998) and non-obese PCOS patients (Marciniak et al 2009). The correlation between leptin and IR is thus still a matter of debate.…”
Section: Leptinmentioning
confidence: 95%